2002
DOI: 10.1103/physreva.65.030101
|View full text |Cite
|
Sign up to set email alerts
|

Linear optics and projective measurements alone suffice to create large-photon-number path entanglement

Abstract: We propose a method for preparing maximal path entanglement with a definite photon number N , larger than two, using projective measurements. In contrast with the previously known schemes, our method uses only linear optics. Specifically, we exhibit a way of generating four-photon, pathentangled states of the form |4, 0 + |0, 4 , using only four beam splitters and two detectors. These states are of major interest as a resource for quantum interferometric sensors as well as for optical quantum lithography and q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 22 publications
(42 reference statements)
0
94
0
Order By: Relevance
“…The N-fold coincidence measurement of all N detectors will give P N , the outcome of a NOON state projection measurement. Notice that state projection methods have been proposed before [3,4,5]. But those methods require 2N photons for the generation of N -photon NOON state.…”
Section: Noon State Projection Measurementmentioning
confidence: 99%
“…The N-fold coincidence measurement of all N detectors will give P N , the outcome of a NOON state projection measurement. Notice that state projection methods have been proposed before [3,4,5]. But those methods require 2N photons for the generation of N -photon NOON state.…”
Section: Noon State Projection Measurementmentioning
confidence: 99%
“…It was shown recently that these states may be conditionally generated with the help of linear optics, single photon sources and photodetectors [14,15,16,17]. We then combine the modes 1 and 2 on a balanced beam splitter and measure the number of photons in output modes 1 and 2 by means of two photodetectors P D 1 and P D 2 with single-photon resolution.…”
Section: Quantum State Truncationmentioning
confidence: 99%
“…Schemes for probabilistic preparation of Fock states [9], arbitrary superpositions of Fock states of single-mode field [10,11], and superpositions of classically distinguishable states (Schrödinger-cat-like states) [12,13], have been found. Several setups for the generation of twomode N -photon path-entangled states have been suggested [14,15,16,17,18]. Recently, the experimental conditional preparation of a single-photon Fock state with negative Wigner function has been reported [19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when arbitrarily many auxiliary modes are available, one does not need the very weak nonlinearities assumed to be essential for these purposes. Subsequently, it was shown that the same resources (linear optics and projective measurements) can be used to create highly nonclassical number states [2,3]. These states are important for applications such as quantum lithography and quantum interferometry [4,5].…”
mentioning
confidence: 99%